Diterimanya Hasil Belajar Evaluasi Pembelajaran Kejuruan: Peran Mediasi Motivasi Belajar - Sukoco, Muhammad Galuh Aji Mahardika Lanang; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the influence of learning facilities and learning environment on student learning outcomes in the Vocational Learning Evaluation course, as well as to determine the role of learning motivation mediation. This study uses a quantitative method with a survey approach. The research sample was taken using a purposive sampling technique totaling 69 students of the Automotive Engineering Education Study Program, Semarang State University (UNNES) class of 2022 who took the Vocational Learning Evaluation course. The research will be carried out in the fifth semester of 2024. Data processing is carried out using the SmartPLS 4 application. The research instrument is in the form of a questionnaire that has been validated by experts. This study tested direct and indirect (intervening) hypotheses, with independent variables, namely learning facilities (X1) and learning environment (X2), dependent variables of learning outcomes (Z1), and learning motivation (Y1) as intervening variables. Data analysis included convergent validity tests, discriminant validity, reliability estimation, R-Square values, F-Square, hypothesis tests, and Goodness of Fit (GoF). The results of the study show that the model used is reliable. The path coefficient between learning facilities and learning outcomes was 0.377, learning facilities to learning motivation was 0.317, learning environment to learning outcomes was 0.312, learning environment to learning motivation was 0.527, and learning motivation to learning outcomes was 0.282. The total indirect effects between learning facilities and learning outcomes were 0.089, while between learning environment and learning outcomes were 0.149. Positive values in each relationship indicate a positive influence between variables. The results of this study prove that learning motivation plays a significant role as a mediating variable in influencing student learning outcomes. These findings emphasize the importance of providing adequate learning facilities and a conducive learning environment to increase student motivation and learning outcomes in the Vocational Learning Evaluation course.